Determinants of the financial solvency of the municipal boxes in Perú (2012-2016). - Pinto Ranilla, Paulino Celso (2019)
The present research work analyzes the economic and financial factors that contribute to the strengthening of the financial solvency of the 12 municipal savings banks that operate in Peru and, on the other hand, the relationship that exists between the global capital ratio and the Altman Z score. The study was carried out with data from the financial statements of the last five years (2012-2016) of each of the 12 institutions that are valid as of December 31, 2016. The results obtained indicate that the factors that have the greatest incidence in the strengthening of the financial solvency of the entities are related to income and profits generated by each of the institutions, likewise, there is a relationship between Altman's Z score and the global capital ratio. The multifactorial model has been obtained that allows making future estimates of financial solvency indicators that, coupled with the analysis of simulations, contribute to risk management in the CMACs.